2020
DOI: 10.1093/jisesa/ieaa089
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the N- and P-Fertilization Effect of Black Soldier Fly (Diptera: Stratiomyidae) By-Products on Maize

Abstract: To meet the growing demand for an alternative animal protein source, the Black Soldier Fly (BSF) (Hermetia illucens) industry is expanding. Thus, the valuation of its byproducts, foremost BSF frass, is getting more economic and ecological weight. Three different residues, BSF frass, larval skins, and dead adult flies, were compared with a mineral and an organic commercial fertilizer in a pot trial with maize (Zea mays L., [Poales: Poaceae]). byproducts were applied in three nutrient-based application rates (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 46 publications
0
28
1
2
Order By: Relevance
“…Due to its high content in nitrogen (N), phosphorus (P) and potassium (K) as well as the potential presence of beneficial microorganisms (Poveda et al, 2019), the use of frass as a fertilizer could help in reducing the use of agrochemicals. For instance, frass from black soldier fly (Hermetia illucens L.) was successfully used as an organic fertilizer to promote the growth of maize (Beesigamukama et al, 2020a;Gärttling et al, 2020) and ryegrass (Menino et al, 2021). In addition, frass from mealworm (Tenebrio molitor L.) showed great potential to be used as a partial or a complete substitute for mineral NPK fertilizer for the growth of barley (Houben et al, 2020) while stimulating soil microbial (Poveda et al, 2019) and earthworm activity (Dulaurent et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high content in nitrogen (N), phosphorus (P) and potassium (K) as well as the potential presence of beneficial microorganisms (Poveda et al, 2019), the use of frass as a fertilizer could help in reducing the use of agrochemicals. For instance, frass from black soldier fly (Hermetia illucens L.) was successfully used as an organic fertilizer to promote the growth of maize (Beesigamukama et al, 2020a;Gärttling et al, 2020) and ryegrass (Menino et al, 2021). In addition, frass from mealworm (Tenebrio molitor L.) showed great potential to be used as a partial or a complete substitute for mineral NPK fertilizer for the growth of barley (Houben et al, 2020) while stimulating soil microbial (Poveda et al, 2019) and earthworm activity (Dulaurent et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Barley treated with mealworm frass applications had similar biomass, nitrogen, phosphorus, and potassium concentrations in comparison to inorganic fertiliser treatments. Maize treated with black soldier fly larvae digestate produced statistically comparable yields to other organic fertilisers, though these yields were significantly lower than the standard inorganic fertiliser (Gärttling et al, 2020). These studies provide further evidence that application in a controlled environment can provide similar benefits to currently adopted fertiliser regime.…”
Section: Use Of Insect Frass As Fertilisermentioning
confidence: 63%
“…The fact that seldom these trials showed a decrease in production -as was reported by Alattar et al [39], when comparing processed food waste via Microaerobic Fermentation and BSF larvae biodigestion as soil fertilizers in maize, or Gärttling et al [40], with a BSF frass in a low nutrient potting soil -may not mean that, in the overwhelming majority of experimental trials, the results with entomocompost compete with mineral fertilizers; it should be noted that on the one hand, the implementation of field trials is often preceded by a prior study of the feasibility of the hypothesis and, on the other hand, that regrettably a large proportion of the trials that do not confirm the hypothesis are not reported.…”
Section: Data In the Context Of The Trinomial "Soil X Plant X Fertilizer"mentioning
confidence: 77%